2020
DOI: 10.1007/s42600-020-00105-4
|View full text |Cite
|
Sign up to set email alerts
|

Application of machine learning time series analysis for prediction COVID-19 pandemic

Abstract: Purpose Coronavirus disease is an irresistible infection caused by the respiratory disease coronavirus 2 (SARS-CoV-2). It was first found in Wuhan, China, in December 2019, and has since spread universally, causing a constant pandemic. On June 3, 2020, 6.37 million cases were found in 188 countries and regions. During pandemic prevention, this can minimize the impact of the disease on individuals and groups. A study was carried out on coronavirus to observe the number of cases, deaths, and recovery cases world… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 33 publications
0
25
0
1
Order By: Relevance
“… 15 For infectious diseases in general, this method has been shown to be reasonably accurate and reliable. 16 18 It takes into account the more recent observations and exponentially reduces the weights of older observations. 19 The SES model for this study had been carried out using R package fpp2 .…”
Section: Methodsmentioning
confidence: 99%
“… 15 For infectious diseases in general, this method has been shown to be reasonably accurate and reliable. 16 18 It takes into account the more recent observations and exponentially reduces the weights of older observations. 19 The SES model for this study had been carried out using R package fpp2 .…”
Section: Methodsmentioning
confidence: 99%
“…They concluded that ARIMA and TBAT models performed better for seven countries out of ten countries. [ 27 ] compared different forecasting methods to choose the best method for forecasting deaths due to COVID-19 in the world. These methods include simple average, moving average, naive method, Holt linear trend method, single exponential smoothing, ARIMA and Holt-Winters method.…”
Section: Introductionmentioning
confidence: 99%
“…Even looking at a simple average model from other papers, we can see that the RNN application has produced much better results, indicating that neural networks produce the depth needed to produce accurate results [6].…”
Section: Discussionmentioning
confidence: 94%